Does High School Homework Increase Academic Achievement? - Charlene Marie Kalenkoski; Sabrina Wulff Pabilonia (Institute for the Study of Labor (IZA), 2014)
Although previous research has shown that homework improves students' academic achievement, the majority of these studies use data on students' homework time from retrospective questionnaires, which are less accurate than time-diary data. However, most time-diary data sets do not contain outcome measures, and thus are limited in the questions they can answer. One data set that does have both time-diary and outcome information is the combined Child Development Supplement (CDS) and the Transition to Adulthood Survey (TA) of the Panel Study of Income Dynamics. Students complete time diaries as part of the CDS and then a few years later provide information on outcomes in the TA. The CDS provides us with time diaries for both weekdays and weekend days, providing a good picture of homework over the course of a week rather than on just a single day. For high school graduates, we explore the effects of time spent on homework on two measures of academic achievement: high school GPA and college attendance by age 20. We find that homework time increases the probability of college attendance for boys. In addition, when we look at homework performed as a sole activity, we find that homework increases high school GPA for boys.
Keywords: I2; J22; J24; 330; academic achievement; homework; GPA; human capital; education